2015
DOI: 10.1186/s12920-015-0139-4
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide DNA methylome reveals the dysfunction of intronic microRNAs in major psychosis

Abstract: BackgroundDNA methylation is thought to be extensively involved in the pathogenesis of many diseases, including major psychosis. However, most studies focus on DNA methylation alteration at promoters of protein-coding genes, despite the poor correlation between DNA methylation and gene expression.MethodsWe analyzed differentially methylated regions and differentially expressed genes in patients with schizophrenia and bipolar disorder and normal subjects. Gene expression and DNA methylation were analyzed with R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 57 publications
2
18
0
Order By: Relevance
“…Interestingly, in the frontal cortex and anterior cingulate, only a few differentially methylated regions overlapped with promoters, whereas a greater proportion occurred in introns and intergenic regions (Xiao et al, 2014). A similar pattern was found in another study, where a high percent of DMRs was found in introns and repeat elements (Zhao et al, 2015) in the brain region BA9. In this particular study, hypermethylated DMRs significantly overlapped with long intergenic non-coding RNAs (lincRNAs), while hypomethylated DMRs significantly overlapped with introns, as well as with short and long interspersed nuclear elements.…”
Section: Dna Methylation In Bdsupporting
confidence: 89%
See 3 more Smart Citations
“…Interestingly, in the frontal cortex and anterior cingulate, only a few differentially methylated regions overlapped with promoters, whereas a greater proportion occurred in introns and intergenic regions (Xiao et al, 2014). A similar pattern was found in another study, where a high percent of DMRs was found in introns and repeat elements (Zhao et al, 2015) in the brain region BA9. In this particular study, hypermethylated DMRs significantly overlapped with long intergenic non-coding RNAs (lincRNAs), while hypomethylated DMRs significantly overlapped with introns, as well as with short and long interspersed nuclear elements.…”
Section: Dna Methylation In Bdsupporting
confidence: 89%
“…Genome-wide methylation differences have also been analyzed in blood (Dempster et al, 2011; Houtepen et al, 2016; Li et al, 2015; Sabunciyan et al, 2015; Walker et al, 2016) and in different post-mortem brain regions, such as the BA9 (Zhao et al, 2015), frontal cortex (Mill et al, 2008; Xiao et al, 2014), anterior cingulate (Xiao et al, 2014), and cerebellum (Chen et al, 2014) from BD patients and controls.…”
Section: Dna Methylation In Bdmentioning
confidence: 99%
See 2 more Smart Citations
“…DNA methylation difference of human leukocyte antigen (HLA) complex group 9 gene (HCG9) 90 was replicated in an independent sample set. 91 Other studies showed altered methylation statuses of drebrin-like protein, 88 PIK3R1, BTN3A3, NHLH1, SLC16A7, 92 MSX1, CCND2, DAXX, 93 and hsa-mir-7-3, 94 though the findings are not consistent across studies. When the bulk brain is homogenized and methylation analysis is performed, the obtained results almost reflect the DNA methylation levels of glial cells.…”
Section: Epigenomementioning
confidence: 95%